Electroanalysis of Pharmaceuticals on Boron‐Doped Diamond Electrodes: A Review - Sousa, Camila P. (2020)
Boron‐doped diamond (BDD) electrodes possess outstanding physical, chemical, and electronic properties and have been successfully, yet in a limited way, explored in the electroanalysis of substances with therapeutic action (analgesics, antipyretics, antibiotics, anti‐inflammatories, antihypertensives, antidepressants, vitamins, and others) in diverse milieus (pharmaceutical formulations, urine, serum, whole blood, surface waters, seawaters, groundwater, wastewaters, etc.). Therefore, in this Review, a broad overview of the available scientific information on recent progress and achievements of the application of bare or modified BDD electrodes to the bioanalytical and environmental detection of pharmaceutical compounds is presented. The main parameters, for example boron concentration, applied operational conditions during pretreatment, chemical and physical structure, and other influential factors on the electroanalytical BDD electrodes performance, are discussed.